2016
DOI: 10.5935/scd1984-8773.201682814
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate to severe acne vulgaris with an oral isotretinoin similar to the reference product

Abstract: Conflict of interests: the study was sponsored by Germed Pharma Ltda, however the methodology, execution and analysis of obtained results were carried out by involved institutions researchers, without any interference from the pharmaceutical industry. Treatment of moderate to severe acne vulgaris with an oral isotretinoin similar to the reference productTratamento da acne vulgar moderada a grave com isotretinoína oral similar ao produto referência

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, a eliminação de medicamentos contendo esse princípio ativo é lenta, de forma que, no mínimo durante 30 dias após o uso é necessário evitar a gravidez 16,23 , sendo ainda importante a assinatura do Termo de Consentimento Informado, demonstrando ciência dos riscos 24 .…”
Section: Resultsunclassified
“…Particularly, oral isotretinoin looks more effective at achieving prolonged remission after treatment than other choices such as oral antibiotics, making it a potentially more durable option for acne patients. This study has significant implications for the current and future management of patients with hormonal or environmental acne [19,21,22].…”
Section: Discussionmentioning
confidence: 97%
“…These processes limit the proliferation of Propionibacterium acnes, a critical factor in the development of acne lesions, and can lead to improvements in skin clarity and acne severity overall. In 90% of patients, the inflammatory lesions were observed to be decreased [21]. Oral isotretinoin is more successful than oral antibiotics in attaining durable remission after therapy, according to an assessment of the relevant research.…”
Section: Discussionmentioning
confidence: 99%